2020
DOI: 10.1016/j.stem.2020.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Spatiotemporally Dynamic Wnt-Secreting Niches Regulate Proximal Airway Regeneration and Aging

Abstract: Highlights d Tracheal epithelial b-catenin tightly controls proliferation and differentiation d PDGFRa + lineage comprises Wnt signaling niche necessary for epithelial proliferation d Airway basal stem cell-derived Wnts facilitate differentiation to ciliated cells d Age-related Wnt/b-catenin niche changes drive gland-like epithelial invaginations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 65 publications
0
24
1
Order By: Relevance
“…Once the micro-environment balance is disrupted, AEC senescence is initiated [ 34 ]. Cross-talk, such as that among IGF1, TGF-β, and Wnt, can also induce AECs senescence [ 35 37 ]. Blockade of a single signaling pathway can inhibit IPF to some extent; however, other pathways would be activated in compensation.…”
Section: Discussionmentioning
confidence: 99%
“…Once the micro-environment balance is disrupted, AEC senescence is initiated [ 34 ]. Cross-talk, such as that among IGF1, TGF-β, and Wnt, can also induce AECs senescence [ 35 37 ]. Blockade of a single signaling pathway can inhibit IPF to some extent; however, other pathways would be activated in compensation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as described above, Wnt signals facilitate MEC contribution to proximal airway regeneration following severe injury 48 . At the cellular level, a recent group identified that a subset of Pdgfrα+ cells in the intercartilaginous zone are transiently, dynamically activated to secrete Wnt ligand that signals to the airway epithelium to promote its proliferation 64 . During differentiation, β-catenin activity is increased in air–liquid interface (ALI) cultures, a culturing system used to model airway epithelial remodeling, and enhances specification for the ciliated cell lineage 61 .…”
Section: Proximal Airway Homeostasis and Regenerationmentioning
confidence: 99%
“…During differentiation, β-catenin activity is increased in air–liquid interface (ALI) cultures, a culturing system used to model airway epithelial remodeling, and enhances specification for the ciliated cell lineage 61 . In vivo, this phase is also driven by Wnt secretion from K5+ ABSCs that are necessary for differentiation to the ciliated cell fate 64 .…”
Section: Proximal Airway Homeostasis and Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…While mesenchymal cells (e.g., fibroblasts) are the major regulators of ECM deposition and organization, our data suggest that NOTCH3 signaling may have a similar role in regulating airway epithelial-derived ECM production. Similar to NOTCH signaling, Wnt/β-catenin signaling also plays a crucial role in regulating cell fate decisions in the human lung [52,[62][63][64][65][66][67]. Therefore, our data demonstrating NOTCH3 activation modulates expression of multiple genes in the Wnt/β-catenin signaling pathway suggest that NOTCH3 may cross-talk with this pathway to regulate airway epithelial differentiation.…”
Section: Discussionmentioning
confidence: 66%